Bensonetal.CanisHybridZoneMicrosatelliteData - Benson, John F.; Patterson, Brent R.; Wheeldon, Tyler J. (Dryad Digital Repository, 2012)
Microsatellite Allele data collected from individual wolves, coyotes, and hybrids (each has individual id, data on separate rows) in central Ontario.